Current state and prospects for improving the institutions of exemption from criminal liability and punishment - Biebayeva, A.A.; Kalguzhinova А.М.; Ozbekov D.О. (Bulletin of the Karaganda University “Law Series”, 2021)
One of the key areas of the criminal policy of the Republic of Kazakhstan is the humanization of criminal legislation through a gradual reduction in the scope of criminal repression by improving the institution of exemption from criminal liability, expanding the grounds for exemption from criminal punishment and parole. The authors of this article comprehensively studied the content of the institutions of exemption from criminal liability and exemption from punishment in the previously existing criminal laws: Criminal Codes of the RSFSR of 1922 and 1926, the Criminal Code of the Kazakh SSR of 1959, and the Criminal Code of the Republic of Kazakhstan of 1997. In addition, they analyzed the novelties of the Criminal Code of the Republic of Kazakhstan of 2014, corresponding to the idea of restorative justice, which is gradually entering the legal reality of Kazakhstan. The main part of the article defines the essence of establishing a surety, which is classified by the Law of the Republic of Kazakhstan as of December 27, 2019 as a type of exemption from punishment. The legal nature is revealed, the grounds and conditions enshrined in the law, the procedure for applying this type of exemption from punishment are analyzed, and its importance in stimulating positive post-criminal behavior is shown. The scientific recommendations proposed by the authors are aimed at overcoming the most common problems in the practice of applying the rules governing the conditions and procedure for exemption from criminal liability and punishment.